WORKSHOP ON INQUIRY LEARNING BASED VIRTUAL LABORATORY IN MAGELANG FOR PREPARING NATURAL SCIENCES TEACHER IN 21ST CENTURY: AN EVALUATION OF IMPLEMENTATION’S PROGRAM - Siswanto Siswanto; Eli Trisnowati; Fifit Firmadani; Sri Haryati; Dwi Aryanti; H Nosih Andrianto (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
In 21st century, the learning process must be adjusted to the worth values developing in the 21st century. One of the learning process that suitable on the 21st century learning is inquiry learning that collaborated with virtual laboratory. The aim of this research is to evaluate inquiry-learning workshop based virtual laboratory in Magelang for preparing natural sciences teacher in 21st century. The evaluation has done by using CIPP model (context, input, process, and product). This evaluation model was chosen because we wanted to know the effectiveness extent of the program. The result, in general shows that the program is well implemented. The goal of inquiry program has been reached. This is indicated by implementation indicator has been reached. Several indicators among them is : (1) The teacher has good skill in making learning program preparation (Rencana Program Pembelajaran/RPP); (2) The teacher is able to create student.s worksheet; (3) The teachers is well in carry out teaching practices in the classroom, which is all accordance with the principle of 21st century learning.